Penerapan Kualitas Pelayanan E-Filing Wajib Pajak dalam Penyampaian SPT-Tahunan (Studi Kasus KPP Pratama Cileungsi) - Mulia, Grace Daniel; Wijaya, Komang Adi Sastra; Yasintha, Putu Nomy (CITIZEN CHARTER; Vol 2 No 2 (2022): Administrasi Publik 2022, 2023)
KPP Pratama Cileungsi is responsible for interacting and assisting taxpayers in E-filing their annual tax returns through electronic filing. E-Filing is established by the Decree of the Directorate General for Taxes No. Kep-88/PJ/2004, established by the Directorate General for Taxes No. Kep-88/PJ/2004. It's one of the services we offer. File electronic tax returns for taxpayers online in real time. Time via the Internet and the DGT website or through a provider of tax filing services designated by the DGT. This study aims to analyze the application of the quality of electronic filing services provided by KPP Pratama Cileungsi to taxpayers when submitting annual SPTs. This analysis references Parasuraman and Berry's (2011) five indicators expressed through their theory. The five metrics are Tangibles, Realibility, Responsiveness, Assurance, and Empathy. As a result of this discovery, KPP Pratama Cileungsi still has some indicators flawed when implementing the electronic filing service. Keywords : service quality, E-Filing, KPP Pratama Cileungsi